Smoking impairs and circulating stem cells favour the protective effect of the T allele of the connexin37 gene in ischemic heart disease – A multinational study. (January 2016) - Pitha, Jan; Králová Lesná, Ivana; Hubáček, Jaroslav A.; Sekerková, Alena; Lánská, Věra; Adámková, Věra; Dorobantu, Maria; Nicolescu, Rodica; Steiner, Robert; Ivić, Vedrana; Borbely, Attila; Papp, Zoltan; et al.
Abstract: Background: The connexin 37 (Cx37) gene is considered to be a candidate gene for ischemic heart disease (IHD). We analyzed the association between the C1019 > T (Pro319 > Ser) variant of the Cx37 gene and IHD in patients in the Czech Republic, Croatia, Hungary and Romania with regard to the presence/absence of selected cardiovascular risk factors (RF). In a complementary study, we analyzed the association between the Cx37 gene and circulating stem and endothelial progenitor cells in healthy women. Methods: The study population comprised 2396 patients (663 women) with IHD. The control population comprised 2476 subjects (1, 337 women). Additionally, in 662 healthy women, the association between the Cx37 gene and circulating stem and endothelial progenitor cells was analyzed. Results: The strongest protective effect of the Cx37 T allele was detected in non-smoking patients without diabetes mellitus and hypertension (OR 0.610, 95% CI 0.377–0.990); a similar effect was found in non-smoking men (OR 0.781, 95% CI 0.628–0.971); weaker effect was found in non-smoking women (OR 0.768, 95% CI 0.560–1.050). In non-smoking healthy women, stem cells were significantly higher in TT than in CT and CC carriers (p for trend 0.011). Additionally, non-smoking TT carriers had significantly higher number of stem cells than past and current smoking TT carriers (p for trend = 0.006); no such trend was found in CT and CC carriers. Conclusions: The protective effect of the T allele of the Cx37 gene might be strongly modified by smoking; in women, this effect could be mediated through stem cells. Highlights: We analysed association between connexin37 gene and cardiovascular disease. Patients with ischemic heart disease and control population sample were studied. We found strong protective effect of Cx37g T allele limited to non-smoking patients. Stem cells were significantly higher in healthy non-smoking women – TT carriers. Protective effect of the T allele of the Cx37 gene is strongly modified by smoking.